Effects of different plant populations on yield of different soybean (Glycine max (L.) merrill) varieties in a smallholder sector of Zimbabwe - Madanzi, Tendai; Chiduza, C.; Kageler, Richardson S.J.; Muziri, Tavagwisa (Asian Network for Scientific Information, 2014)
A study was conducted at Chinyika Resettlement Area (Chinyudze, Gowakowa, Pfumoiguru and Chinyudze) and at Thornpark Estates (University of Zimbabwe Farm) to evaluate the effects of different plant populations (100 000, 150 000, 200 000, 250 000 plants ha-1) on the yield and yield components of three different specific nodulating soybean varieties during the 2002/2003 (Storm, Safari and Solitaire) and four varieties during the 2003/2004 rainy season (Storm, Safari, Solitaire and Magoye). In 2002/2003 the trial was laid as a 3x4 factorial treatment structure under Randomised Complete Block Design (RCBD) while during the 2003/2004 the trial was laid as a 4x4 factorial treatment structure replicated thrice. Results showed that there was a significant interaction (p<0.05) on yield due to plant population and variety main effects at Pfumoiguru. The highest yield was obtained between 200 000 and 250000 plants ha-1 while the indeterminate grain type of varieties, Safari and Solitaire obtained the highest yield across all sites. Farmers in marginal areas like Chinyika Resettlement Area may plant soybean at between 200000 and 250000 plants ha-1 while indeterminates like Solitaire and Safari may also be considered. In high potential areas like Thornpark Estates, farmers can grow soybean at 250000 plants ha-1 or at the recommended plant population of 300000 plants ha-1 across all varieties except for Magoye which achieved higher yield at 100000 plants ha-1